30+6 years of community seed banking around the world: a good start, but more to be done and learned - Vernooy, Ronnie (NAGRC, LI-BIRD and Bioversity International, 2018)
Six years have passed since the first national meeting of community seed banks in Nepal. Since then, Bioversity International and partners around the world have expanded their capacity development, research and policy advocacy efforts to make community seed banks and the emerging networks of community seed banks more efficient and effective. A series of North-South exchange of experiences took place. New capacity development materials were developed. A number of young researchers researched sustainability and related (novel) issues of importance to community seed banks. In 2018, a proposal was finalized to establish a global community seed banks platform that will support existing community seed banks and national/regional community seed bank networks around the world, scale out their activities and achievements, and contribute to their sustainability